Nanotechnology platforms for antigen and immunostimulant delivery in vaccine formulations - Márquez, Patricio Guillermo (2024)
Vaccines represent a cornerstone in global health history, marking one of the most significant scientific achievements. Initially consisting of live or attenuated microorganisms, vaccines have evolved to include subunit vaccines, which offer greater specificity, safety, and production advantages. However, subunit vaccines require adjuvants due to the low immunogenicity of their antigens. These adjuvants include immunostimulatory molecules and particulate systems, which serve as carriers for both antigens and immunostimulants. The nanoscale dimensions of these particulate systems confer distinct advantages. This review comprehensively discusses FDA andEMA-approved vaccines that incorporate adjuvants, emphasizing the growing use of nanoparticulate adjuvants in enhancing vaccine efficacy and safety. The unique physicochemical properties of nanoscopic systems, such as hydrodynamic size, shape, surface charge, hydrophobicity and degradation profiles are explored, that determine their effectiveness in vaccine formulations.Furthermore, innovations in production scalability and alternative delivery routes, such as oral or transdermalvaccines, offer promising solutions to global vaccine accessibility challenges, particularly in resource-limitedsettings. The ongoing integration of nanotechnology platforms thus continues to expand the potential of vaccines,ensuring safer, more effective, and more accessible solutions for global immunization efforts.